Pemanfaatan Daging Buah Pala (Myristica Fragrans) sebagai Bahan Baku Pembuatan Permen Jelly dengan Variasi Konsentrasi Sukrosa - Andro Lampah; Thelma D. J. Tuju; Lana E. Lalujan (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
The purpose of this study was to determine the sensory properties, water content and sucrose content of Nutmeg’s flesh jelly candy. The research method used was a completely randomized design (RAL) consisting of 5 treatment with varying sucrose variation, namely P1: (30%), P2: (35%), P3: (40%), P4: (45%) and P5: (50%). The results showed that the physicochemical characteristics of jelly candy were water content ranging from 16.6% - 19.3%, sucrose content 36.12% - 53.67%. The most preferred jelly candy sensory test was treatment P3 with 40% sucrose variation with a taste value of 3,60 (like), color 3,80 (like), aroma 3,05 (neutral) and textures 3,80 (like) and differentiating test result with a difference value of 4. Keywords: nutmeg; sucrose; sensory test.